Interpersonal perception, personality, and academic achievement: a dyadic approach for the study of undergraduate performance - Andrés, Amara; Solanas, Antonio; Salafranca, Lluís (Anales de Psicología / Annals of Psychology, 2012)
The present work deals with the quantification of group characteristics by means of dyadic indices. Specifically, the aim of the present study was to explore whether dyadic and individual measures of interpersonal perceptions and personality could be related to academic achievement when dealing with project groups in a real academic setting. 88 undergraduate students formed 22 groups of four people to carry out a course report. After working together throughout the semester, participants filled in an Interpersonal Perception Questionnaire and NEO-FFI and the course report was assessed. Results showed that some dyadic measurements of interpersonal perceptions are associated to the marks obtained in the course report. Furthermore, an exponential regression function is proposed accounting for 50.3% of group marks variance. The predictive results found in the scientific literature revised, that follows an individualistic approach, are no larger than 18%. The results of the present study concur with previous results obtained in a laboratory context supporting the usefulness of the dyadic approach for the study of groups.